Irsyadul Murid Hisab Of The Beginning Islamic Lunar Month On Digital Falak Web-Based - Iqnaul Umam Ashidiqi (Syariah: Jurnal Hukum dan Pemikiran, 2019)
Abstract:The development of astronomy in determining the beginning of the Islamic lunar month has occurred so rapidly, along with the sophistication of technology that makes it easy for users to get information. The digital falak web-based application was made by Ahmad TholhahMa'ruf an astronomy scholar from Islamic boarding school who presented the astronomy books. This web- based application displayed data and calculations in several books of astronomy inclusion including IrsyadulMuridbook. The research method used was qualitative with descriptive approach. The type of data used was library research. The results showed that the algorithm used in the early reckoning of Islamic lunar inIrsyadulMuridbook based on the digital falak web was different toIrsyadulMuridbook. The results of calculating the book IrsyadulMuridwith the digital falak web of celibacy were inappropriate which was done manually within the last 3 years making the results different. So, it could be concluded that the digital Falak web was inaccurate if it was used for rukyat data. Evaluation was necessarily needed, thus hisab(astronomical calculation) result in digital falak web-based would be equivalent to hisab in IrsyadulMuridbook. Keywords:digital falak web,Islamic lunar month,IrsyadulMurid.